Histopathological study of endometrium in abnormal uterine bleeding - S Bhatta; AK Sinha (Association of Clinical Pathologists of Nepal, 2012)
Background: Histopathological evaluation of endometrial samples is essential in the workup of abnormal uterine bleeding. This study was carried out to evaluate patterns of endometrial histological findings in women with abnormal uterine bleeding and to correlate histopathological findings with clinical features. Materials and Methods: One hundred and twenty two patients with diagnosis of abnormal uterine bleeding underwent endometrial sampling. The slides stained with Hematoxylin and Eosin stain were studied. Results: The predominant endometrial histopathological finding was proliferative endometrium 32 cases (26.23%) followed by simple hyperplasia without atypia 22 cases (18.03%). Malignant lesions were more common in patients more than 40 years of age and comprised of 7 cases (5.74%) of all cases. Atrophic endometrium was most common finding in postmenopausal bleeding 8 cases (28.6%) followed by endometrial carcinoma 5 cases (17.9%). Conclusion: Histopathological examination of endometrium should be done generously in women presenting with abnormal uterine bleeding especially after the age of 40 years to rule out malignant pathology. Journal of Pathology of Nepal (2012) Vol. 2, 297-300 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6882